A PAPER SURVEY ON THE IMPACT OF (IT) ON THE QUALITY OF FINANCIAL DATA (CASE STUDY OF MUNICIPALITIES AND TOURISM MINISTRY IN KURDISTAN REGION – IRAQ) - Firas N. Mardan; Farah Qasim Ahmed (QALAAI ZANIST SCIENTIFIC JOURNAL, 2021)
Information technology is a major resource to supply suitable information to help enhance it on the process of rational and managerial decision-making. Information Technologies also contribute to the administration ability to do its functions (for example, planning, control and decision-making), and monitoring the governmental revenue, control the public funds to ensure the safety of its spending and make sure that the decision and administrative procedures subject to the supervision of the office of financial supervision are done according to the operative legalization, then keeping the public funds and manage it well. By doing that, the reports will be presented with full results supreme and legislative authorities in the government, in order to have a strong and fit monitoring and follow-up system. To achieve the aim of this work, the questionnaire has been distributed to the Municipal offices that have a financial activity and have a clear picture about the governmental accounting information system. To achieve the aim of this work, the questionnaire has been distributed to the municipal offices that have a financial activity and have a clear picture about the governmental accounting information system. This study reaches that E-accounting information system in the ministry of municipalities and tourism has basic ingredients that contribute to achieving the medium aims of the system. Where the municipal offices have electronic devices and accounting programs but these systems are different from an office to the other because of their activities and the experiences for the employees.